PEDAFICTION AND REFLECTION: FAMILIARIZING INDONESIAN EFL PRE-SERVICE TEACHERS WITH TEACHER COMPETENCE THROUGH STORIES - Maolida, Elis Homsini; Suherdi, Didi; Setyarini, Sri; Suparman, Asep (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Numerous studies have highlighted the need for competent teachers in today’s classrooms. Many suggest that to meet this demand, the preparation should be stipulated at the pre-service level so, when the graduates become in-service teachers, they are already well-prepared to meet the requirements of competent teachers. This study explores the use of pedafiction stories and reflection to familiarize EFL pre-service teachers with teacher competence. The data were obtained from observation, focus group interviews and reflection papers to be analyzed by using thematic analysis (Braun Clarke, 2022). Forty-two pre-service teachers were involved in six TEFL class sessions focusing on the topic of English Teacher Competence in the Indonesian context. They read and reflected on the pedafiction stories, shared their reflections on the stories through a pair-share activity, and wrote individual reflections. The findings reveal that pedafiction stories exploration and reflection have enabled the pre-service teachers to identify the English teacher competencies shown by the character in the story. Besides, the pre-service teachers could relate the topic of teacher competence to a broader social context. Pedafiction and reflection, to a certain extent, have also contributed to the development of the pre-service teachers’ teaching identity. The findings shed light on the potential of stories and reflective practice for English teacher preparation at the pre-service level.